2020
DOI: 10.3390/jcm10010077
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution—An Overlooked Risk Factor for Idiopathic Pulmonary Fibrosis

Abstract: Air pollution is a major environmental risk to health and a global public health concern. In 2016, according to the World Health Organization (WHO), ambient air pollution in cities and rural areas was estimated to cause 4.2 million premature deaths. It is estimated that around 91% of the world’s population lives in places where air pollution exceeds the limits recommended by the WHO. Sources of air pollution are multiple and context-specific. Air pollution exposures are established risk factors for development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Idiopathic pulmonary fibrosis (IPF) results from repeated micro-injuries to alveolar epithelium, caused by the exposure to various noxious stimuli, leading in genetically predisposed individuals to subsequent dysfunction of the alveolar epithelial cells (AECs), aberrant healing, and diffuse parenchymal fibrosis in the final stage of the pathogenic process (8)(9)(10)(11)(12). As consequence patients with IPF develop progressive dyspnea, the gradual decline of lung function, physical activity limitation, impairment of quality of life, and premature death with a median survival of 3 to 5 years (8,13).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) results from repeated micro-injuries to alveolar epithelium, caused by the exposure to various noxious stimuli, leading in genetically predisposed individuals to subsequent dysfunction of the alveolar epithelial cells (AECs), aberrant healing, and diffuse parenchymal fibrosis in the final stage of the pathogenic process (8)(9)(10)(11)(12). As consequence patients with IPF develop progressive dyspnea, the gradual decline of lung function, physical activity limitation, impairment of quality of life, and premature death with a median survival of 3 to 5 years (8,13).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of pre-existing small foci of fibrosis in the alveolar septal walls is unexplained but as Soweto is a densely populated urban environment this could be consequent to environmental pollutants including exposure to tobacco smoke or previous episodes of unknown lung disease resulting in early interstitial lung disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research investigating the combined effects focuses on the pulmonary system, as the lung is usually the first organ to interact with PM after inhalation. Lung fibrosis is known to be both caused and worsened by ambient PM [ 113 , 114 ]. A study on bleomycin induced lung fibrosis demonstrated that aerobic exercise reduced the severity of inflammation and fibrosis in this model [ 115 ].…”
Section: Evidence On the (Cardiovascular) Health Effects Of Physical Activity And Air Pollution From Animal Studiesmentioning
confidence: 99%